Teleworking in the Covid-19 Pandemic - Christoph Weinert; Tim Weitzel (Business & Information Systems Engineering, 2023)
Teleworkers who live and work in the same space are vulnerable to conflicts between personal life and work (LWC). The Covid-19 lockdowns increased the intensity and risk of LWC and changed telework conditions, confronting teleworkers with difficult personal situations and often ill-equipped telework environments. To develop a better understanding of the effects of different LWC dimensions (e.g., time, strain, behavior) on work exhaustion, job satisfaction, routine and innovative job performance and the role of the IT telework environment among teleworkers in the Covid-19 pandemic, a research model based on a sample of 249 teleworkers was developed and validated. The findings show that LWC has adverse effects on job outcomes and that the IT telework environment moderates these effects. The study contributes to the telework and role conflict literature by revealing the essential role of the IT telework environment and by differentiating between routine and innovative job performance among teleworkers.
Keywords: 000; Teleworking; Work from home; Life-work conflict; Work-home conflict; Role theory; Routine and innovative job performance; Work exhaustion; Job satisfaction